High Sensitive C-Reactive Protein and Lipid Profile Alteration In Subclinical Hypothyroidism for Cardiovascular Risk Assessment - Rajkarnikar, Smrity; Sharma, Vijay Kumar; Baidya, Sujata; Kadel, Pratibha; Tuladhar, Eans Tara; Niraula, Apeksha; Bhattarai, Aseem; Raut, Mithileshwer; Dubey, Raju Kumar; Parajuli, Naresh (Journal of Nepal Health Research Council, 2024)
Background: The purpose of this study was to investigate the association of subclinical hypothyroidism with High sensitive C-reactive protein & lipid profile which can predispose to development of Cardiovascular disease.Methods: This hospital-based comparative cross-sectional study was conducted for a period of six months. A total of 71 patients with subclinical hypothyroidism & 37 healthy control subjects were enrolled for the study. Thyroid hormones, lipid profile, hs- CRP were measured and lipid variables were used to calculate lipid indices. Student t-test were used to compare means & Spearman’s correlation was done to determine the association between variables. ROC curve analysis was used to determine the diagnostic value of tests.Results: Out of 71 cases & 37 control, majority had female preponderance (71.8% in case & 83.8% in control). The mean values between case & control groups for hs-CRP, AIP, LCI and non-HDL cholesterol were statistically significant. There was positive correlation between TSH and hs-CRP (r=0.492, p <0.001), AIP and TSH (r=0.430, p<0.001), LCI and TSH (r=0.269, p =0.005), TSH and non-HDL cholesterol (r=0.308, p=0.001) & AI and LDL (r= 0.712, p<0.001) with weak correlation with statistical significance as per Spearman’s correlation. Area under ROC curve for hs-CRP indicated it as a positive biomarker for CVD assessment.Conclusions: Our findings shows that SCH patients are more at risk of CVD & hs-CRP contributes as a significant marker, thus requiring timely intervention. Lipid indices and AIP must be determined even in patients with a normal lipid profile to improve atherogenic risk.Keywords: Cardiovascular risk; dyslipidemia; hs-CRP; subclinical hypothyroidism.